Biophysical Characteristics of MFS Working Sites in Bangladesh: Barguna, Patuakhali, Khulna, Dinajpur, Rangpur and Nilphamari - Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2023)
Objectives: - To collect the biophysical characteristics of MFS’s districts in Bangladesh. - Collection and analysis of time series climate data (rainfall, max temperature, min temperature) in study districts.